Evaluation of speed–flow characteristics on two-lane highways with mixed traffic. Issue 4 (2nd October 2017) - Saha, Pritam; Sarkar, Ashoke Kumar; Pal, Manish
Abstract: The HCM (Highway Capacity Manual 2010) classifies two-lane rural highway that passes through developed areas as 'Class III' and suggests using Percent Free-Flow Speed (PFFS) as performance measure to define Level Of Service (LOS). Apparently, this performance measure addresses the main limitation associated with using Average Travel Speed (ATS) as a measure of performance. However, larger speed differential under heterogeneous traffic causes error in estimating Free-Flow Speed (FFS) and thus affects PFFS. This implication was examined in the present study using field data collected on a national highway approaching a city. Speed–flow equations were developed and intercept values were compared to the FFS obtained according to HCM guidelines. Comparison confirms a very close agreement between average FFS value and those obtained for different types of vehicle separately except for car. This consequently causes an error in estimating PFFS since the traffic composition consists of significant proportion of car. The possible capacity of the highway section was observed to be around 2300 pc/h for mixed traffic situation.